Risk factors for low back pain after oblique lumbar interbody fusion in patients with low-grade degenerative lumbar spondylolisthesis: a retrospective study - Shuanchi Wang; Jiabao Chen; Zhe Lu (Frontiers in Surgery)
ObjectiveTo investigate the risk factors of low back pain after oblique lumbar interbody fusion (OLIF) in patients with low grade degenerative lumbar spondylolisthesis (DLS).MethodsThis retrospective study included 116 patients with single-level low-grade lumbar spondylolisthesis with low back pain who underwent OLIF surgery in our hospital from December 2017 to October 2020. Demographic, clinical, surgical, and radiological characteristics of this population were analyzed to determine the relationship between these characteristics and the degree of low back pain relief after OLIF.ResultsA total of 116 patients (average age 58.61 ± 7.01 years) were included in this study. Among them, 33 patients had poor improvement of low back pain after surgery, and 83 patients had satisfactory effect after surgery with obvious relief of low back pain. Postoperative disc height increase ≤2.5 mm (P = 0.000) was most correlated with poor improvement of low back pain symptoms after OLIF. The factors positively correlated with poor improvement of low back pain symptoms after OLIF in patients with low-grade degenerative lumbar spondylolisthesis included the increase of spondylolisthesis grade (OR = 17.665; 95%CI: 3.262–95.678 P = 0.001), disc height increase ≤2.5 mm (OR = 34.377; 95%CI: 5.632–209.818 P = 0.000). The factors negatively correlated with poor improvement of low back pain symptoms after OLIF in patients with low-grade degenerative lumbar spondylolisthesis included no osteoporosis (OR = 0.067; 95%CI: 0.013–0.350 P = 0.001), no cage subsidence (OR = 0.208; 95%CI: 0.048–0.903 P = 0.036), duration of preoperative low back pain symptoms ≤36 months (OR = 0.045; 95%CI: 0.007–0.277 P = 0.001).ConclusionsOLIF can significantly improve the low back pain symptoms in patients with low-grade degenerative lumbar spondylolisthesis. High grade of spondylolisthesis before operation, duration of low back pain symptoms more than 36 months, osteoporosis, postoperative cage subsidence, and postoperative segmental disc height improvement less than 2.5 mm are risk factors for low back pain after operation.